A QUEST FOR LITERATURE IN ELT COURSEBOOKS - Gümüşok, Fatma (Journal of History Culture and Art Research, 2013)
The mission of literature in ELT has undergone a change for the last century. Once both a vehicle and an aim for teaching foreign language, literature now seems to remain out of center. Although it has various benefits for language learners, it reaches language classes only when the teacher is willing to make use of it, which is suggested by the studies conducted on teaching literature (Ross, 1991; Timuçin, 2001; Wang, 2009). Following the language teacher, coursebooks are the second primary input source in a classroom. In other words, if a teacher is reluctant to use literary texts in the lesson, the coursebook is the only provider for literature to be benefited. Therefore, this study aims at exploring to what extent literary texts and literary elements are used in ELT coursebooks. ELT coursebooks used in the preparatory schools of state universities in Ankara were analyzed for literary texts and elements. In addition, two ELT coursebook series which were published in the last 20 years and are not used anymore were analyzed in order to see whether ELT coursebooks differ with regard to the quantity of literary texts and elements in the last 20 years. In total, 22 coursebooks from different levels were analyzed. The finding reveals that ELT coursebooks contain bits and pieces of literature and there has been decrease in the number of literary texts in the currently used coursebooks.